Synkretyzm mistyczny jako zagrożenie wiary - Nowicki, Andrzej Stefan (Studia Pastoralne, 2026)
Mystical syncretism is a form of religious syncretism. The criticism of Christian mysticism from the dominance of liberal Protestantism, and the thesis of the identity of any mystical experiences substantially contributed to the formation of mystical syncretism. The dynamic development of the phenomenon seen in many countries of Western Europe, raises a reasonable dispute with the idea of a mystical syncretism on the part of Catholic theology. The main areas of controversy center on threats such as: the loss of their own religious identity, the danger of creating fertile ground for the spread of so-called „new religion” and the threat of further development of interreligious dialogue.